2020
DOI: 10.1186/s12891-020-03673-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects on health and process outcomes of physiotherapist-led orthopaedic triage for patients with musculoskeletal disorders: a systematic review of comparative studies

Abstract: Background Physiotherapist-led (PT-led) orthopaedic triage is an evolving model of care for patients with musculoskeletal disorders. Objectives for this study were to establish the current evidence body on the impact of PT-led orthopaedic triage on health, quality, and service outcomes for patients referred for orthopaedic consultation, compared with standard (orthopaedic surgeon) care. Methods Medline, EMBASE, Scopus and CINAHL were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 69 publications
(240 reference statements)
3
14
0
Order By: Relevance
“…Historically, less than 7% of non‐urgent patients reviewed in clinic required surgery. Similar low surgical conversion rates have been reported in other orthopaedic clinics, 5 and highlight inefficiencies within clinical pathways.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Historically, less than 7% of non‐urgent patients reviewed in clinic required surgery. Similar low surgical conversion rates have been reported in other orthopaedic clinics, 5 and highlight inefficiencies within clinical pathways.…”
Section: Introductionsupporting
confidence: 76%
“…Within physiotherapy‐led models, advanced or extended scope physiotherapists triage, assess and/or treat patients referred to orthopaedic clinics. Studies have shown that these models can reduce orthopaedic clinic waitlists, 5 increase conversion to surgery rates (thus improving efficiency) 5,6 and are cost‐effective 6,7 . Additionally, clinical outcomes are comparable to traditional models of care, 5,8 re‐referral rates are low, 9 and patients report high levels of satisfaction 5,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, to our knowledge no current literature on this topic exists. Furthermore, recent systematic reviews have shown that musculoskeletal triage by professionals, such as extended scope physiotherapists, can possibly reduce healthcare utilization and help manage GP workload (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapists and orthopaedic surgeons have similar high diagnostic accuracy compared to magnetic resonance imaging of musculoskeletal disorders (75% respectively 81%), and significantly higher accuracy than family practice and internal medicine physicians who have an accuracy of 35% [ 25 ]. Moreover, Samsson et al [ 26 ] concluded that physiotherapists and orthopaedic surgeons determined similar diagnoses, and recommended similar management for patients with musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%